The Molecular Mechanism of Chronic High-Dose Corticosterone-Induced Aggravation of Cognitive Impairment in APP/PS1 Transgenic Mice - Zhang, Shen-Qing; Cao, Long-Long; Liang, Yun-Yue; Wang, Pu (Frontiers in Molecular Neuroscience, 2021)
Clinical studies have found that some Alzheimer’s disease (AD) patients suffer from Cushing's syndrome (CS). CS is caused by long-term release of excess glucocorticoids (GCs) from the adrenal gland, which in turn, impair brain function and induce dementia. Thus, we investigated the mechanism of the effect of corticosterone (CORT) on the development and progression of AD in a preclinical model. Specifically, the plasma CORT levels of 9-month-old APP/PS1 Tg mice were abnormally increased, suggesting an association between GCs and AD. Long-term administration of CORT accelerated cognitive dysfunction by increasing the production and deposition of β-amyloid (Aβ). The mechanism of action of CORT treatment involved stimulation of the expression of BACE-1 and presenilin (PS) 1 in vitro and in vivo. This observation was confirmed in mice with adrenalectomy (ADX), which had lower levels of GCs. Moreover, the glucocorticoid receptor (GR) mediated the effects of CORT on the stimulation of the expression of BACE-1 and PS1 via the PKA and CREB pathways in neuroblastoma N2a cells. In addition to these mechanisms, CORT can induce cognitive decline in APP/PS1 Tg mice by inducing apoptosis and decreasing the differentiation of neurons.